2022
DOI: 10.1038/s41598-022-13935-2
|View full text |Cite
|
Sign up to set email alerts
|

Baseline peripheral neuropathy was associated with age and a prognostic factor in newly diagnosed multiple myeloma patients

Abstract: Multiple myeloma (MM) is an incurable plasma cell hematological malignancy. Bortezomib has become the primary drug in the treatment of patients with MM. However, its negative effects, especially peripheral neuropathy (PN), affect the patients’ life quality and treatment continuity. However, there are few studies on baseline PN of MM, and little is known of the impact of baseline PN on the prognosis of MM patients. Therefore, we reviewed the clinical data of newly diagnosed MM patients in our center, explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…However, we and others have previously reported that spinal microglial reaction in cancer-induced bone pain models is a highly variable occurrence that may not reflect the clinical reality (43,44). Instead, the neuropathic component of MIBP is in line with clinical reports describing baseline peripheral neuropathy in a proportion of MM patients (45,46), which is also used as a prognostic factor of chemotherapy induced peripheral neuropathy and treatment outcome in this patient population (47). These results, in combination with our observation of periosteal nerve sprouting, suggest that medications targeted to neuropathic pain patients may be useful to treat a fraction of myeloma bone pain patients.…”
Section: Discussionsupporting
confidence: 71%
“…However, we and others have previously reported that spinal microglial reaction in cancer-induced bone pain models is a highly variable occurrence that may not reflect the clinical reality (43,44). Instead, the neuropathic component of MIBP is in line with clinical reports describing baseline peripheral neuropathy in a proportion of MM patients (45,46), which is also used as a prognostic factor of chemotherapy induced peripheral neuropathy and treatment outcome in this patient population (47). These results, in combination with our observation of periosteal nerve sprouting, suggest that medications targeted to neuropathic pain patients may be useful to treat a fraction of myeloma bone pain patients.…”
Section: Discussionsupporting
confidence: 71%
“…In MM, many prognostic and predictive biomarkers are of high value in predicting therapeutic efficacy, as well as indicating PFS and OS. Translocations, copy number abnormalities and mutations at the gene level, minimal residual disease (MRD) measured by flow cytometry and next-generation sequencing (NGS) detection, blood biopsy detection of circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), and baseline clinical characters have gradually become advanced biomarkers ( 31 33 ). However, these indicators are still not perfect, and certain examinations are invasive or costly.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Peripheral neuropathy (PN) is a common complication of MM that mainly manifests as sensory neuropathies and motor neuropathies in severe cases. 2 Multiple myeloma peripheral neuropathy (MMPN) can be divided into disease-related PN and drug-related PN. In disease-related PN, sensory modalities may be affected, resulting in axonal sensorimotor neuropathy with a length-dependent pattern of axonal regrowth.…”
Section: Introductionmentioning
confidence: 99%